Myxomycete with the ability to accumulate heavy metals. Hemitrichia serpula - Kryvomaz, Т. І.; Minter, D. W.; Michaud, A. (CABI, 2019)
Diagnostic features. Very conspicuous; habit usually entirely plasmodiocarpous and sessile; sporocarps unmistakable, looking like miniature versions of the Indian sweet jalebi, or pretzels; spore ornamentation a raised episporic network appearing to give the spore a border in optical section (compound microscope magnifications > ×400).
Keywords: myxomycetes; міксоміцети; Hemitrichia serpula